Study of the Photographer as a Study: Looking Inside Duncan Winder’s Home (sometime between c1962 and 1965) - Wood, Peter (Architectural History Aotearoa, 2022)
In recent years there has been a small increase in research addressing the architectural photography of Duncan Winder. While this scholarship adds to critical appreciation of his skill and productivity as a recorder of New Zealand buildings, of his personal life we remain largely ignorant. To know an artist’s life well does not guarantee a transparent view into their creative mind, but in the case of Winder we are so bereft of insight into his private life that the only way we have to explore him biographically is through his photographs. Overwhelmingly, Winder’s archived oeuvre demonstrates a photographer determined to keep his own image firmly behind the lens. Foreground shadows and, on occasion, a blurred reflection, signal rare glimpses of the photographer at work. But otherwise, his common technique of bringing a hidden character to the camera suggests a determined effort by Winder to not only remain outside the view of the lens, but apart from the entirety of the scene being recorded. Against this pattern, this paper identifies seven images drawn from the Winder archive that present as being of a common domestic interior dated to the 1960s. Contrary to the proliferation of architect-designed rooms that dominate Winder’s archive, these photographs show a modest home whose domestic character might be best categorised as "bach-like." Added to this, the composition of each photograph is unusually casual for Winder’s work, and they read more as impulsive snap-shots than considered views. When content details are correlated against archival information it can be faithfully concluded that this interior is the home of Duncan Winder. The remainder of the paper interprets one of these images – "House interior, study" - as a knowing self-portrait by the photographer, and the visual scene is interrogated for evidence of Winder’s inner world.